2020
DOI: 10.3389/fonc.2020.01712
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in Incidence and Mortality of Waldenström Macroglobulinemia: A Population-Based Study

Abstract: Background: The incidence of Waldenström macroglobulinemia (WM) has increased in certain groups over several decades in the United States. It is unclear whether the increasing incidence is associated with mortality trends. Methods: The incidence and incidence-based mortality (IBM) rates were obtained from the Surveillance, Epidemiology, and End Results (SEER) database (1980-2016) with SEER * Stat software. The secular trends stratified by demographic characteristics were analyzed by joinpoint regression. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 40 publications
0
23
2
Order By: Relevance
“…3,21,22 In two other populationbased studies, the incidence initially increases until the late 1990s/early 2000s, after which it stabilised. 6,23 Unlike these studies, an increase in incidence was not observed in our present study. This difference could be due to stable registration and diagnostic practices in the Netherlands.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…3,21,22 In two other populationbased studies, the incidence initially increases until the late 1990s/early 2000s, after which it stabilised. 6,23 Unlike these studies, an increase in incidence was not observed in our present study. This difference could be due to stable registration and diagnostic practices in the Netherlands.…”
Section: Discussioncontrasting
confidence: 99%
“…Both entities are hereafter collectively referred to as LPL/WM, a disease primarily affecting individuals aged >60 years 3 . The annual age‐standardised incidence rate (ASR) of LPL/WM is approximately three per million person‐years in Western countries 4–6 . The natural history of LPL/WM is heterogeneous, with many patients remaining asymptomatic for years without need for treatment, while others require treatment early 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance, epidemiology, and end results data studies have demonstrated the annual incidence rate to be higher in Caucasian population (0.52 per 100,000; 95% CI: 0.50–0.53) compared with African American population (0.29 per 100,000, 95% CI: 0.26–0.33). 4 Waldenström macroglobulinemia lies on a spectrum of disorders ranging from an immunoglobulin M (IgM) monoclonal gammopathy of undetermined significance (MGUS), to asymptomatic/smoldering WM and eventually symptomatic disease. 1 The common underlying feature in these disorders is the presence of circulating monoclonal IgM protein.…”
Section: Introductionmentioning
confidence: 99%
“…It is a relatively uncommon non-Hodgkin lymphoma (NHL) with an incidence rate of 0.3 per 100,000 persons [ 2 ]. WM is a disease of the elderly, with a predilection for males more than females, and for Caucasians more than other populations [ 3 ]. There may be genetic and environmental factors which contribute to the development of WM, but no clear causative factors have been identified in the pathogenesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There may be genetic and environmental factors which contribute to the development of WM, but no clear causative factors have been identified in the pathogenesis [ 4 ]. Based on a recent Surveillance, Epidemiology, and End Results (SEER) analysis, the five-year survival rate has improved from 48% to 69% during the period from the 1980s to the 2010s [ 3 ].…”
Section: Introductionmentioning
confidence: 99%